Long-term results of intratympanic prednisolone injection in patients with idiopathic sudden sensorineural hearing loss. (September 2013) - Filipo, Roberto; Attanasio, Giuseppe; Cagnoni, Laura; Masci, Eleonora; Russo, Francesca Y.; Cartocci, Giulia; Di Mario, Alessia; Covelli, Edoardo
Abstract Conclusion: The results demonstrate the stability of the efficacy over time of the intratympanic prednisolone protocol and they suggest that the spontaneous recovery does not significantly influence the long-term evaluation of intratympanic therapy. A 10-day follow-up after 3 days of intratympanic prednisolone administration can be considered a sufficient period to evaluate the effectiveness of the undertaken therapy. Objective: To assess the stability of the efficacy over time of intratympanic steroid therapy for patients with idiopathic sudden sensorineural hearing loss. Methods: A total of 122 patients received an intratympanic steroid injection of prednisolone daily for 3 days. Audiograms were performed before therapy and at 10 days and 1 year after therapy. Successful recovery was defined as complete and partial recovery using Siegel's criteria and complete and marked recovery following Furuhashi's criteria. Results: The comparison of audiometric data at study entry, at 10 days, and at 1 year after the treatment showed a statistically significant improvement of the mean pure tone audiometry. The evaluation of the hearing outcomes demonstrated a statistically significant improvement, with similar success rates when evaluated 10 days and 1 year after the treatment. Comparing the hearing outcomes at 1 year with the results at 10 days, no significant difference was detected between these two time points.